Agro-morphological and molecular characterization of Argentine maize (Zea mays L.) landraces of ‘Cristalino Colorado’ race - Raquel Alicia Defacio; Natalia Mercedes Paz; Ana Rosa Schlater; Marcelo Edmundo Ferrer; Sergio Jorge Bramardi (Genetic Resources)
Despite the high variability of Argentine maize (Zea mays L.) landraces, they are scarcely used by breeders due to the limited knowledge available about the genetic merit of these materials. In this study, we evaluated agro-morphological and molecular traits of 36 landraces of the ‘Cristalino Colorado’ race from Buenos Aires province, Argentina. Fifteen agro-morphological traits and five polymorphic microsatellite markers located on different chromosomes (48 alleles) were used. A principal component analysis was performed using average values of agro-morphological traits across two environments. Molecular markers were subjected to a principal coordinate analysis. A generalized procrustes analysis was used to evaluate agro-morphological and molecular traits together, showing seven groups. Distance between agro-morphological and molecular data had an average value of 0.24 and the range varied between 0.02 (ARZM01017) and 0.45 (ARZM01082). The results show that Argentine landraces of the ‘Cristalino Colorado’ race are a valuable source of new alleles for crop improvement. Studies of this type facilitate the selection of landraces for introduction in genetic breeding programmes and for the establishment of core collections.